Electron redistribution and acid site of tungsten-doped CeTiOx with oxygen vacancies. (3rd April 2021) - Kim, Myungju; Park, Gwanhee; Shin, Minchul; Kim, Hong-dae; Cho, Dae-Seung; Lee, Heesoo
ABSTRACT: The enhancement of surface acidity for tungsten-doped CeTiOx was investigated through electronic structure. Tungsten doping increased the ratio of Ce 3+ from 12.0% to 29.6%, which was confirmed by XPS. The doped tungsten was present as W 5+ in a ratio of 71.5%. In O K -edge XAS spectra, increase in I e g / I t 2 g indicated the formation of oxygen vacancies through tungsten doping. The decrease in W 5d-eg peak intensity demonstrated the occupation of the W 5d orbital by electrons formed at the oxygen vacancies. The enrichment of W 5+ was owing to transfer of electrons to 5d-eg orbital of tungsten rather than to cerium ions. The acid sites were analysed using FTIR and NH3 -TPD. The peak intensity of Brønsted acid sites and amount of NH3 desorption increased from 66.2 to 136.1 µmol g −1 with tungsten doping. The doped tungsten formed Brønsted acid sites and led to enhanced surface acidity and catalytic activity.